Socioeconomic differentials in recurrent ischaemia and mortality after acute myocardial infarction. Issue 4 (1st April 2001) - Barakat, K; Stevenson, S; Wilkinson, P; Suliman, A; Ranjadayalan, K; Timmis, A D
Abstract : OBJECTIVE: To examine the influence of socioeconomic deprivation on case fatality following acute myocardial infarction. DESIGN: Prospective cohort observational study. SETTING: General hospital. PATIENTS: 1417 white and south Asian patients admitted with acute myocardial infarction between January 1988 and December 1996, and classified by the Carstairs socioeconomic deprivation score of the enumeration district of residence. MAIN OUTCOME MEASURES: 30 day and one year survival. RESULTS: There was little variation across deprivation groups in age, sex, or smoking status, though a higher proportion of patients from more deprived enumeration districts were diabetic and of south Asian origin, and a higher proportion of them developed Q wave infarction and left ventricular failure. There was no appreciable variation in clinical treatment with deprivation. Patients from more deprived enumeration districts had a higher risk of recurrent ischaemic events (death, recurrent myocardial infarction, or unstable angina) over the first 30 days: event free survival (95% confidence interval (CI)) of the most deprived quartile was 0.79 (95% CI 0.74 to 0.83) compared with 0.85 (95% CI 0.80 to 0.88) in the least deprived quartile. The unadjusted hazard ratio corresponding to an increase from the 5th to 95th centile of the deprivation distribution was 1.54 (95% CI 1.02 to 2.32), and 1.59 (95% CI 1.03 to 2.44) after adjustment for age, sex, racial group, diabetes, acute treatment with thrombolysis and aspirin, and left ventricular failure. Survival from 30 days to one year, however, did not show a socioeconomic gradient (hazard ratio adjusted for the same variables was 1.07 (95% CI 0.68 to 1.70)). CONCLUSIONS: In patients hospitalised with acute myocardial infarction, there is a strong association between early recurrent ischaemic events and socioeconomic deprivation that is not accounted for by clinical presentation or treatment. This association appears to be attenuated over time.